Efeitos da suplementação de vitamina D e treinamento físico aeróbico sobre a função muscular e composição corporal de pacientes em hemodiálise crônica - Vogt, Barbara Perez [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Background: function and muscle mass depletion is frequent in hemodialysis patients, as well as vitamin D deficiency. Vitamin D supplementation exerts positive effects on muscles, and clinical trials combining vitamin D supplementation and physical training have promoted improvements on functional capacity and muscle quality in elderly. Objective: to assess the effects of vitamin D supplementation and intradialytic aerobic training (IDAT) on biochemical parameters, body composition, and muscle function in patients on maintenance hemodialysis. Methods: clinical trial with two arms: randomized, controlled, and double-blind for vitamin D, and randomized, controlled and open-label for IDAT. Patients were randomized in one of the four groups: vitamin D supplementation and IDAT, placebo and IDAT, vitamin D supplementation, and placebo. Muscle mass was assessed by dual-energy X-ray absorptiometry and muscle function was assessed by handgrip strength. Intervention lasted 16 weeks. IDAT program was performed using cycle ergometer, three times a week during hemodialysis session. Vitamin D supplementation was cholecalciferol 50,000 IU per week and vitamin D status was evaluated by serum 25-hydroxyvitamin D (25(OH)D) levels. Results: twenty-nine patients were enrolled in this trial. Nine were excluded during the intervention. Serum vitamin D significantly rose in both groups supplemented with cholecalciferol (baseline: 30.1 ± 6.26 ng/ml; post-intervention: 41.3 ± 9.85 ng/ml; p<0.001). There was a significant interaction between interventions improving triglycerides and HDL-cholesterol. There was significant correlation between variation of serum 25(OH)D and CRP, and variation of serum 25(OH)D and handgrip strength. Vitamin D supplementation had a significant effect on the increase of handgrip strength and BMI. It was not possible to identify whether this weight gain corresponded to lean mass or body fat, since both presented no differences among groups. Conclusion: cholecalciferol supplementation and IDAT interacted improving lipid profile in maintenance hemodialysis patients. Cholecalciferol supplementation promoted muscle function improvement and body weight gain.

Introdução: Depleção de massa e de função muscular é comum em pacientes em hemodiálise, bem como a deficiência de vitamina D. A suplementação de vitamina D tem efeitos positivos no músculo e ensaios clínicos que combinaram suplementação de vitamina D e treinamento físico promoveram melhora em testes de capacidade funcional e qualidade do músculo em idosos. Objetivo: Avaliar os efeitos da suplementação de vitamina D e treinamento aeróbico intradialítico (TAID) sobre parâmetros bioquímicos, composição corporal e função muscular de pacientes em hemodiálise. Metodologia: ensaio clínico com dois braços: randomizado, controlado e duplo cego para vitamina D, e randomizado, controlado e aberto para TAID em indivíduos em hemodiálise. Os pacientes foram randomizados em um dos quatro grupos: suplementação com vitamina D + TAID, placebo + TAID, suplementação com vitamina D, e placebo. Massa muscular foi avaliada por DEXA e função muscular foi avaliada pela força de preensão manual. A intervenção teve duração de 16 semanas. O programa de exercício aeróbico foi realizado em bicicleta ergométrica, três vezes por semana, durante a sessão de hemodiálise. A suplementação de vitamina D foi de 50 000 UI/semana de colecalciferol e status de vitamina D foi avaliado pela concentração sérica de 25-hidroxivitamina D (25(OH)D). Resultados: vinte e nove pacientes foram incluídos no ensaio. Nove foram excluídos durante a intervenção. Vitamina D sérica aumentou em ambos os grupos suplementados com colecalciferol (pré-intervenção: 30.1 ± 6.26 ng/ml; pós-intervenção: 41.3 ± 9.85 ng/ml; p<0.001). Houve interação significativa entre as intervenções melhorando triglicerídeos e HDL-colesterol. Foi encontrada correlação negativa entre alteração de 25(OH)D sérica e do PCR e positiva entre alteração de 25(OH)D sérica e da força de preensão manual. Suplementação de vitamina D apresentou efeito significante no aumento da força de preensão manual e do IMC. Não foi possível identificar se o ganho de peso correspondeu à massa magra ou gordura corporal, porque não houve diferença significativa entre os grupos. Conclusão: suplementação de colecalciferol e TAID interagiram na melhora do perfil lipídico em pacientes em hemodiálise crônica. Suplementação de colecalciferol promoveu melhora da função muscular e aumento de peso corporal.
Effect of vitamin D supplementation and intra dialytic aerobic training on muscle function and body composition in maintenance hemodialysis patients
Keywords: Colecalciferol; Composição corporal; Força de preensão manual; Hemodiálise; Treinamento físico; Body composition; Cholecalciferol; Handgrip strength; Hemodialysis; Physical training